PERAN OPERATOR SEKOLAH DALAM MENGELOLA SISTEM DATA INFORMASI SEBAGAI PENJAMINAN MUTU PELAYANAN PENDIDIKAN DI SMP NEGERI 1 TELUKJAMBE TIMUR KARAWANG - Suryana Saputra (Universitas Negeri Medan, 2020)
Abstrak: Education now requires a foundation that must be built, namely realizing its position as a producer of educational services. Schools must understand well the needs of an increasingly complex society, especially followed by the rapid development of information IT. Research with the title